The use of apparel cad technology in pedagogical training among technical universities in Ghana - Boateng, Ophelia; Marfo Ayesu, Solomon; Komla Asinyo, Benjamin; Crentsil, Tinothy (Indonesian Journal of Education and Social Sciences, 2025)
The study investigated the use of apparel CAD technology in pedagogical training among technical universities in Ghana. The study respectively drew 285 respondents from two public universities, i.e., Kumasi Technical University, Accra Technical University, and Sunyani Technical University in Ghana. The overall population of the study was 285 randomly sampled from the three public universities. The study employed questionnaires as a data collection tool. The data gathered were 285 responses representing 100%. The data was analysed using pie charts, and frequency tables. The study findings show that there is minimal training and inadequate usage of clothing computerised design technology (CCDT). This was brought about by the lecturers' poor instruction and learning resources, the students' limited industrial exposure, and the lack of a competent CAD studio, hardware, and software for clothing design. The instruction and implementation of clothing CAD technology that students received, according to graduates, instructors, and students themselves, did not prepare them or the students to meet the industrial labour need. Therefore, there is a gap between industrial labour demand and university products. It was concluded that teaching and learning materials should be made available, universities' human capital should be well-equipped and motivated, and curricula should be restructured through broad stakeholder consultation. The study finally recommends that the universities should fully invest in the required CAD technology to provide the necessary facilities and equipment and provide lecturers with the needed resources and motivation to restructure the program's fate in our academic space.